Epidemiologia Clássica e Molecular de Klebsiella pneumoniae resistente em hospitais terciários de Uberlândia – MG - Ramirez, Camila Peredo (2025)
The emergence and spread of β-lactam-resistant Klebsiella pneumoniae strains, particularly those resistant to carbapenems, pose a significant threat to therapeutic efficacy, resulting in high mortality rates. Studying the epidemiology of infections caused by carbapenem-resistant K. pneumoniae (CRKP) is crucial for understanding the dissemination of virulence and resistance genes, as well as the distribution of mortality rates associated with CRKP isolates in the city of Uberlândia. Initially, the study aimed to analyze the spread of K. pneumoniae producing ESBLs and carbapenemases in hospital settings. Additionally, it sought to identify variables associated with mortality due to K. pneumoniae bacteremia, with a particular focus on the impact of targeted combination therapy. To address the first objective, K. pneumoniae isolates were randomly selected from two tertiary hospitals in Minas Gerais, Brazil. These carbapenem-resistant isolates were assessed for the presence of blaCTX-M-15, blaKPC, blaNDM, blaSHV, blaTEM, blaVIM, qnrA, aadA1, entB, kfu, ureA, wabG, allS, Aero, and rmpA genes using polymerase chain reaction (PCR). All blaCTX-M-15 PCR amplicons were analyzed for genetic relationships via pulsed-field gel electrophoresis (PFGE). For the second objective, medical records of 109 patients (collected between 2011 and 2019) were reviewed to evaluate risk factors for CRKP bacteremia. The relationship between patients' demographic and clinical data and multidrug resistance (MDR) was analyzed. The primary outcomes were 30-day mortality rates. Excess mortality was calculated for the following groups: multidrug- resistant K. pneumoniae, carbapenem-resistant K. pneumoniae, and carbapenem-sensitive K. pneumoniae. A univariate analysis was conducted to identify factors associated with 30-day mortality. In the first phase of the study, a high prevalence of resistance and virulence genes was observed in K. pneumoniae isolates. Resistance genes included ESBLs (blaCTX-M-15 25.5%, blaTEM 96.1%, blaSHV 92.2%) and carbapenemases (blaKPC 31.4%, blaVIM 54.9%, blaNDM 25.5%). Virulence genes such as entB (84.3%), kfu (86.3%), ureA (90.2%), wabG (94.1%), allS (11.8%), Aero (68.6%), and rmpA (9.8%) were also commonly found. Respiratory infections (32.7%) were the most frequent, followed by rectal colonization (24.7%). Genotyping identified three dominant clones (A, B, and E) with distinct geographic distribution patterns. For the second objective, it was demonstrated that 64.2% of isolates were resistant to carbapenems, and inappropriate empirical therapy was observed in 62.4% of patients. In the univariate analysis, hemodialysis was identified as a mortality risk factor (p=0.0238). Carbapenem-resistant strains were associated with an excess mortality rate of 12.95%, while multidrug-resistant strains had the lowest excess mortality rate (4.51%). This study highlights the alarming prevalence of resistance and virulence genes in K. pneumoniae, emphasizing its role in severe infections. The high carbapenem resistance rates and associated excess mortality underscore the urgent need for improved prevention, control measures, and personalized antimicrobial therapies in hospital settings. These findings provide critical insights into advancing infection management strategies and reducing the burden of multidrug-resistant infections.